Digital Literacy Integration Model and Creative Thinking for Enhancing Vocational Student Competencies in the Society 5.0 Era - Cici Suriyani; Yeka Hendriyani; Fahmi Rizal; Asrul Huda (STKIP Singkawang, 2025)
The vocational education sector faces significant challenges in preparing graduates who meet industry demands in the digital era. Data from SMKN 1 Padang shows that the achievement of vocational competencies is still not optimal with aspects of knowledge 65%, skills 70%, occupational safety and health 70%, and work tests 70%. This study aims to analyze the influence of Digital Literacy, Learning Styles, and Critical Thinking on Student Competencies of SMKN 1 Padang. This study uses a quantitative approach with an explanatory survey design. The sample consisted of 81 active students of SMKN 1 Padang selected using a purposive sampling technique. Data were collected through a structured questionnaire with a Likert scale of 1-5 and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS. The research model showed excellent psychometric quality with all constructs having adequate validity and reliability (Cronbach's Alpha > 0.925, AVE > 0.597). Structural model evaluation revealed that Digital Literacy (β = 0.275, p = 0.008), Learning Styles (β = 0.266, p = 0.050), and Critical Thinking (β = 0.411, p = 0.004) had a positive and significant effect on Student Competencies. The model explained 82.3% of the variance in Student Competencies (R² = 0.823). The results of the study confirmed the importance of integrating Digital Literacy, appropriate Learning Styles, and the development of Critical Thinking in improving Student Competencies in Vocational High Schools. These findings provide important implications for the development of holistic learning strategies in vocational education.